The Relationship Between Family Educational Inputs and Middle School Students’ Academic Achievement: A Moderated Mediated Effects Analysis - Yueying Xu; Yuandong Shang; Peijie Lu (Journal of Advanced Research in Education, 2024)
In order to clarify the intrinsic mechanism of the influence of family education input on junior high school students’ academic performance, this study constructed a moderated mediation model based on the S-C-R theory, and used the Family Education Input Scale, the Social Support Scale, the Academic Efficacy Scale, and the Academic Performance Questionnaire to conduct the survey. The results showed that: (1) family education input has a positive predictive effect on academic achievement; (2) family education input can significantly predict junior high school students’ academic achievement through the mediating effect of academic efficacy; (3) with the increase of social support, the predictive effect of family education input on academic efficacy becomes more obvious. Conclusion: The moderated mediation model of family education input affecting junior high school students’ academic achievement was established, in which academic efficacy mediated between family education input and academic achievement, and social support moderated between family education input and academic efficacy.